Finerenone and left ventricular hypertrophy in chronic kidney disease and type 2 diabetes - Gerasimos Filippatos; Stefan D. Anker; George L. Bakris; Peter Rossing; Luis M. Ruilope; Andrew J.S. Coats; Stephan vonHaehling; Piotr Ponikowski; Giuseppe M.C. Rosano; Meike Brinker; Alfredo E. Farjat; Luke Roberts; et al. (ESC Heart Failure)
Abstract Aims Left ventricular hypertrophy (LVH) has been associated with an increased risk of cardiovascular (CV) disease and linked to increased morbidity and mortality. In patients with chronic kidney disease (CKD) and type 2 diabetes (T2D), hypertension is common, and patients with these co‐morbidities additionally have a high prevalence of LVH. This analysis of the prespecified pooled FIDELITY analysis comprising the randomized, double‐blind, placebo‐controlled, multicentre FIDELIO‐DKD and FIGARO‐DKD phase III studies aimed to explore the CV and kidney effects of finerenone, a nonsteroidal mineralocorticoid receptor antagonist, in patients with CKD and T2D stratified by a diagnosis of LVH at baseline. Methods and results A diagnosis of LVH in the FIDELITY patient population was determined at baseline using investigator‐reported electrocardiogram (ECG) findings. The two efficacy outcomes, assessed by baseline LVH, were the composite CV outcome of time to CV death, non‐fatal myocardial infarction, non‐fatal stroke, or hospitalization for heart failure (HHF), and a composite kidney outcome of time to onset of kidney failure, a sustained decrease in estimated glomerular filtration rate (eGFR) ≥57% from baseline over ≥4 weeks, or kidney‐related death. Safety outcomes by baseline LVH were reported as treatment‐emergent adverse events. At baseline out of 13 026 patients in FIDELITY, 96.5% had hypertension and 9.6% had investigator‐reported LVH. The relative risk reduction for the composite CV and kidney outcomes with finerenone versus placebo was lower in the LVH subgroup; however, the treatment effect of finerenone was not modified by baseline LVH for either outcome (Pinteraction = 0.1075 for composite CV outcome and Pinteraction = 0.1782 for composite kidney outcome). Analysis of the composite CV outcome components showed a greater reduction in the risk of HHF versus placebo for patients with baseline LVH compared with those without (Pinteraction = 0.0024). Overall safety events were comparable between the LVH subgroups and treatment arms. Treatment‐emergent hyperkalaemia was observed more frequently with finerenone versus placebo, but discontinuation rates were low in both treatment arms and between LVH subgroups. Conclusions In conclusion, the overall CV and kidney benefits of finerenone versus placebo were not modified by the presence of LVH at baseline, with overall safety findings being similar between LVH subgroups. A greater benefit was observed for HHF in patients with versus without LVH, suggesting that LVH may be a predictor of the treatment effect of finerenone on HHF.